E-Commerce and Word of Mouth Influence on Member Satisfaction at Alfafa Tour & Travel - Hadi, Lukman; Hananto, Joko (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this research was to find out how big the relationship between the two independent variables, namely E-Commerce (Electronic Commerce) and Word of Mouth (Word of Mouth Marketing) is to Member Satisfaction at Alfafa Tour & Travel. The sampling technique is random sampling. Where the samples are taken randomly, each population and sample has the same chance. Based on the calculation results, there is a positive influence of E-Commerce (Electronic Commerce) on Member Satisfaction, an analysis result value of 0.926 is obtained, so it can be concluded that the influence is very strong. So it is proven by testing the E-Commerce (Electronic Commerce) hypothesis on the Member Satisfaction variable, the t value obtained is = 11.507 > t0.05 (64) = 1.670, then Ho is rejected and Ha is accepted, which means there is sufficient evidence that there is a significant influence. There is a positive influence of Word of Mouth (Word of Mouth Marketing) on ??the Member Satisfaction variable, with a value of 0.893, so it can be concluded that the influence is very strong. And prove it by testing the hypothesis of the Word of Mouth variable (Word of Mouth Marketing) on ??the Member Satisfaction variable, the value obtained is t = 68.784 > t0.05 (64) = 1.670, then H is rejected and Ha is accepted which means there is evidence that there is a significant influence. Simultaneously there is a positive influence between the variables E-Commerce (Electronic Commerce) and Word of Mouth (Word of Mouth Marketing) on ??the Member Satisfaction variable calculated with an R value of 0.894 which has a positive value and a very strong level of influence while the R Square value is 0.798 or 79.8%, so the two independent variables can influence each other on the dependent variable. Then, using the ANOVA or Fcount test, a value of 124,756 was obtained, which is greater than Frabel (65) of 2,750 with a significance level of 0.000 because 0.000 < 0.05, so it can be said that the E-Commerce variable and the Word of Mouth variable (Word of Mouth Marketing) on ??the Member Satisfaction variable together has a very significant influence.